Size-Strain Analysis of Iron-Excess Mn-Zn Ferrite Nanoparticles Using Synchrotron Diffraction and Its Correlation with Magnetic Saturation and Isoelectric pH - Ichikawa, Rodrigo U.; Parra, Joao P. R. L. L. [UNESP]; Martins, Murillo L.; Yoshito, Walter K.; Saeki, Margarida J. [UNESP]; Turrillas, Xavier; Martinez, Luis G. (Amer Scientific Publishers, 2018)
Iron-excess Mn-Zn ferrite nanoparticles were prepared by coprecipitation with sodium hydroxide (NaOH) at different concentrations (0.1, 0.2, 0.5 and 1.0 mol/L). The results of X-ray diffraction (XRD) analysis using Whole Powder Pattern Modeling (WPPM) showed that higher concentrations of NaOH promote crystallite growth and broader dispersion in crystallite sizes. Energy dispersive X-ray spectroscopy indicates that zinc loss is noticeable when [NaOH] = 0.2 mol/L. XRD revealed also a significant less-crystalline phase contribution alongside the main peaks of the nanocrystalline cubic spinel ferrite phase. The less-crystalline fraction is lower for the ferrite obtained with 0.2 mol/L of NaOH, being about 50% and more than 70% for the other samples. Despite of the less-crystalline fraction and the excess of iron, no secondary phases were detected. The Warren curves showed that the concentration of NaOH significantly influences the microstrain in the crystallites, being smaller for the sample obtained with NaOH at 0.2 mol/L. The sample prepared with this condition presented the better properties to be used as magnetic tracer in clinical diagnoses combining small mean crystallite size, low microstrain, which resulted in materials with higher magnetic saturation and high surface charge under blood pH.
Keywords: Mn-Zn Ferrites; Nanoparticles; Size-Strain Analysis; X-ray Synchrotron Diffraction